Current insights into the hepatic microenvironment and advances in immunotherapy for hepatocellular carcinoma - Zhao, Ming; Huang, Hui; He, Feng; Fu, Xiangsheng (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer and shows high global incidence and mortality rates. The liver is an immune-tolerated organ with a specific immune microenvironment that causes traditional therapeutic approaches to HCC, such as chemotherapy, radiotherapy, and molecular targeted therapy, to have limited efficacy. The dramatic advances in immuno-oncology in the past few decades have modified the paradigm of cancer therapy, ushering in the era of immunotherapy. Currently, despite the rapid integration of cancer immunotherapy into clinical practice, some patients still show no response to treatment. Therefore, a rational approach is to target the tumor microenvironment when developing the next generation of immunotherapy. This review aims to provide insights into the hepatic immune microenvironment in HCC and summarize the mechanisms of action and clinical usage of immunotherapeutic options for HCC, including immune checkpoint blockade, adoptive therapy, cytokine therapy, vaccine therapy, and oncolytic virus-based therapy.